2008
DOI: 10.1097/fbp.0b013e32830cd80f
|View full text |Cite
|
Sign up to set email alerts
|

Animal models of depression in dopamine, serotonin, and norepinephrine transporter knockout mice: prominent effects of dopamine transporter deletions

Abstract: Antidepressant drugs produce therapeutic actions and many of their side effects via blockade of the plasma membrane transporters for serotonin (SERT/SLC6A2), norepinephrine (NET/SLC6A1) and dopamine (DAT/SLC6A3). Many antidepressants block several ofthese transporters; some are more selective. Mouse gene knockouts of these transporters provide interesting models for possible effects of chronic antidepressant treatments. To examine the role of monoamine transporters in models of depression DAT, NET and SERT KO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
110
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(122 citation statements)
references
References 61 publications
10
110
1
1
Order By: Relevance
“…Notwithstanding that the monoamine hypothesis may be an oversimplification unlikely to fully explain the complexity of human depression (68 -71), unbalance of monoaminergic systems is considered a key factor of the disease, and a prominent neurochemical feature of animal models (72,73). Here we found several distinctions in monoaminergic function between wild-type and PrP C -null mice.…”
Section: Discussionmentioning
confidence: 51%
“…Notwithstanding that the monoamine hypothesis may be an oversimplification unlikely to fully explain the complexity of human depression (68 -71), unbalance of monoaminergic systems is considered a key factor of the disease, and a prominent neurochemical feature of animal models (72,73). Here we found several distinctions in monoaminergic function between wild-type and PrP C -null mice.…”
Section: Discussionmentioning
confidence: 51%
“…Although the contributions of more than a single monoamine-related mechanisms, including dopamine-related mechanisms, were suggested by previous studies (Miller et al, 1996;Perona et al, 2008), the selective serotonin reuptake inhibitor FL, as well as AT and CL, the drugs which inhibit the reuptake of serotonin and norepinephrine, caused -mental model, which is consistent with previous studies (Rygula et al, 2006;Strekalova et al, 2006). On the other hand, in the IM-NC group of mice co-treated with AT, -erence index were not caused by NC, which antagonized the IM-induced attenuated preference for sucrose in the IM-NC group without the co-treatment (Figs.…”
Section: Effects Of "Antidepressant" Drugsmentioning
confidence: 99%
“…25 Further, supporting the validity of this approach, even with the small group sizes reported in these initial studies, we found reversal of depression diagnosed with the pilot equation in experiment 2 for the FST, a standard screen of antidepressant efficacy. 48,49 The depression identified with the equation, therefore, meets the criterion proposed by McKinney and Bunney.…”
mentioning
confidence: 97%